A biopsychosocial approach to processes and pathways in the development of overweight and obesity in childhood: Insights from developmental theory and research. (15th February 2019) - Russell, Catherine G.; Russell, Alan
Summary: Childhood obesity has reached alarming proportions in many countries. There is consensus that both biological (especially genetic) and environmental (including psychosocial) factors contribute to weight gain and obesity in childhood. Research has identified extensive risk or predictive factors for childhood obesity from both of these domains. There is less consensus about the developmental processes or pathways showing how these risk factors lead to overweigh/obesity (OW/OB) in childhood. We outline a biopsychosocial process model of the development of OW/OB in childhood. The model and associated scholarship from developmental theory and research guide an analysis of research on OW/OB in childhood. The model incorporates biological factors such as genetic predispositions or susceptibility genes, temperament, and homeostatic and allostatic processes with the psychosocial and behavioral factors of parenting, parental feeding practices, child appetitive traits, food liking, food intakes, and energy expenditure. There is an emphasis on bidirectional and transactional processes linking child biology and behavior with psychosocial processes and environment. Insights from developmental theory and research include implications for conceptualization, measurement, research design, and possible multiple pathways to OW/OB. Understanding the developmental processes and pathways involved in childhood OW/OB should contribute to more targeted prevention and intervention strategies in childhood.